Environmental and economic assessment of switching from heavy fuel oil to natural gas in industrial boilers and furnaces: Case of Cameroon, a low-income country - Koumi Ngoh, Simon; Epessé Missé, Samuel; Moungnutou Mfetoum, Inoussah (Frontiers in Energy Research, 2022)
This paper analyzes the environmental and economic impact of switching fuel in industrial boilers and furnaces. This analysis, performed over 5 years, reveals that the total emissions thus avoided are 85,069 tons of CO2, 17,240 kg of CH4, 4,310 tons of N2O, and 6,630 tons of SOx. The total equivalent CO2 emissions avoided is around 87,802 tons over the decade 2012–2021. Switching results in a significant reduction in greenhouse gases: 17.8% of CO2 emissions, 66.7% of CH4 emissions, and 83.3% of N2O emissions. Analysis conducted at the boiler level shows that CO2 and CO emissions would decrease, respectively, by 2.5% points and 1.05 ppm points when natural gas is used. The same observation is made for SOx and NOx emissions, for which decreases of 188.3 and 236.7 ppm points are recorded. Additionally, the substitution of heavy fuel oil for natural gas enables an increase in thermal efficiency by 3.3% points.